Ibuprofen-loaded chitosan/poly(maleic anhydride-alt-vinyl acetate) submicronic capsules for pain treatment. (July 2013) - Iurea (Raţă), Delia Mihaela; Popa, Marcel; Chailan, Jean-François; Tamba, Bogdan Ionel; Tudorancea, Ionut; Peptu, Cătălina Anişoara
A new approach to prepare polymeric capsules was developed to obtain an efficient controlled release system for pain treatment. Capsules with a mean diameter between 400 and 1000 nm were prepared using an interfacial condensation method between a natural polymer, chitosan, and a synthetic one, poly(maleic anhydride- alt -vinyl acetate). The influence of different reaction parameters on capsule diameter and properties was investigated. Zeta-potential determinations indicated a good stability of the capsules in aqueous solution containing KCl. Scanning electron microscopy confirmed the submicron dimensions and the spherical shape of the capsules. The thermal properties of the capsules were determined by differential scanning calorimetry and thermogravimetric analysis. In addition, these particles presented a good swelling capacity, which was influenced by the reaction parameters used in this study (molar ratio between the two polymers, the volume ratio between aqueous and organic phase, the amount of surfactant and the reaction time). The ibuprofen loading and release capacity were influenced by the swelling degree. In vivo, the ibuprofen-loaded capsules presented a delayed effect in peripheral pain inhibition and a sustained effect in central pain inhibition.